2022
DOI: 10.1155/2022/8929418
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Targeted Intervention plus Comprehensive Nursing on the Quality of Life and Nursing Satisfaction in Multiple Traumas

Abstract: Objective. To explore the effect of targeted intervention plus comprehensive nursing on quality of life and nursing satisfaction of patients with multiple traumas. Methods. Totally 68 cases with multiple traumas admitted to Xishan People’s Hospital from September 2018 to September 2019 were recruited and randomized into a control group and a study group via the random number table method, with 34 cases in each group. The control group received conventional nursing, and the study group adopted targeted interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%